Bigger than ourselves: the Southgate narrative and the search for a sense of common purpose. Issue 1 (27th August 2020) - Clavane, Anthony; Long, Jonathan
Abstract: The paper examines two 'turns' in English national sporting culture, 'Beckhamisation' and 'Southgatism', and their contribution to an 'imagined community' through processes of 'banal nationalism'. It examines the critiques of various academic and media commentators to demonstrate the link between the trappings of sport (in this case football), and people's understanding of 'us' and 'them'. Music/songs, flags, language, multi-cultural representation, team ethos and espoused values, are not just signifiers, but have a pivotal part to play in representing, repressing and resisting particular forms of Englishness. The focus here is on those national sporting occasions that all too often have been associated with virulent forms of nationalism. We conclude that Southgatism holds out more hope for a progressive sporting patriotism than did its Beckhamite predecessor, but that this has yet to be tested in the febrile cauldron (the 'hostile environment' for immigrants and Brexit) currently forging English national identity.